Testing classic theories of migration in the lab - Batista, Cátia (2018)
We use incentivized laboratory experiments to investigate how potential migrants make decisions between working in different destinations in order to test the predictions of different classic theories of migration. We test theories of income maximization, migrant skill-selection, and multi-destination choice and how the predictions and behavior under these theories vary as we vary migration costs, liquidity constraints, risk, social benefits, and incomplete information. We show how the basic income maximization model of migration with selection on observed and unobserved skills leads to a much higher migration rate and more negative skill-selection than is obtained when migration decisions take place under more realistic assumptions. Second, we find evidence of a home bias, where simply labelling a destination as “home” causes more people to choose that location. Thirdly, we investigate whether the independence of irrelevant alternatives (IIA) assumption holds. We find it holds for most people when decisions just involve wages, costs, and liquidity constraints. However, once we add a risk of unemployment and incomplete information, IIA no longer holds for about 20 percent of our sample.